Modeling and optimizing the integrated problem of closed-loop supply chain network design and disassembly line balancing - Özceylan, Eren; Paksoy, Turan; Bektaş, Tolga (Transportation research. Part E, Logistics and transportation review, 2014)
•CLSC network optimization and DLB problems are integrated.•A nonlinear integer programming formulation is presented.•Numerical examples are presented showing cost savings that can be achieved by solving the integrated problem.•Sensitivity analyses are conducted on various parameters. This paper describes an integrated model that jointly optimizes the strategic and tactical decisions of a closed-loop supply chain (CLSC). The strategic level decisions relate to the amounts of goods flowing on the forward and reverse chains. The tactical level decisions concern balancing disassembly lines in the reverse chain. The objective is to minimize costs of transportation, purchasing, refurbishing, and operating the disassembly workstations. A nonlinear mixed integer programming formulation is described for the problem. Numerical examples are presented using the proposed model.